The effect of robot speed on comfortable passing distances - Neggers, Margot M. E.; Cuijpers, Raymond H.; Ruijten, Peter A. M.; IJsselsteijn, Wijnand A. (Frontiers in Robotics and AI, 2022)
Robots navigate ever more often in close proximity to people. In the current work, we focused on two distinctive navigational scenarios: passing and overtaking a person who is walking. In the first experiment, we compared nine different passing distances for a humanoid robot and found that human comfort increased with passing distance and that their relationship could be described by an inverted Gaussian. In the second experiment, we validated this relationship for an industrial autonomous robot and extended the study to also include overtaking distances and different robot moving speeds. The results showed that overtaking was considered to be less comfortable than passing but that the overtaking distance had a similar relationship with human comfort. Human comfort decreases with a higher robot movement speed. Results obtained through location trackers furthermore showed that people actively take a larger distance from the robot when it starts its trajectory closer to them. The current results can be used to quantify human comfort in environments where humans and robots co-exist and they can be used as input for human-aware navigational models for autonomous robots.